Nanoparticle‐based targeted cancer strategies for non‐invasive prostate cancer intervention. Issue 9 (16th April 2018) - Farina, Nicholas H.; Zingiryan, Areg; Vrolijk, Michael A.; Perrapato, Scott D.; Ades, Steven; Stein, Gary S.; Lian, Jane B.; Landry, Christopher C.
Abstract : Prostate cancer is screened by testing circulating levels of the prostate‐specific antigen (PSA) biomarker, monitoring changes over time, or a digital rectal exam. Abnormal results often lead to prostate biopsy. Prostate cancer positive patients are stratified into very low‐risk, low‐risk, intermediate‐risk, and high‐risk, based on clinical classification parameters, to assess therapy options. However, there remains a gap in our knowledge and a compelling need for improved risk stratification to inform clinical decisions and reduce both over‐diagnosis and over‐treatment. Further, current strategies for clinical intervention do not distinguish clinically aggressive prostate cancer from indolent disease. This mini‐review takes advantage of a large number of functionally characterized microRNAs (miRNA), epigenetic regulators of prostate cancer, that define prostate cancer cell activity, tumor stage, and circulate as biomarkers to monitor disease progression. Nanoparticles provide an effective platform for targeted delivery of miRNA inhibitors or mimics specifically to prostate tumor cells to inhibit cancer progression. Several prostate–specific transmembrane proteins expressed at elevated levels in prostate tumors are under investigation for targeting therapeutic agents to prostate cancer cells. Given that prostate cancer progresses slowly, circulating miRNAs can be monitored to identify tumor progression in indolent disease, allowing identification of miRNAs for nanoparticle intervention before the crucial point of transition to aggressive disease. Here, we describe clinically significant and non‐invasive intervention nanoparticle strategies being used in clinical trials for drug and nucleic acid delivery. The advantages of mesoporous silica‐based nanoparticles and a number of candidate miRNAs for inhibition of prostate cancer are discussed. Abstract : The flowchart of prostate cancer screening, diagnosis, and treatment is based on the 2017 NCCN Guideline recommendations (full version available at NCCN.org ). We posit that assessment of prostate cancer associated microRNAs in circulation can complement current standard‐of‐care algorithms to provide personalized information on cancer cell‐related activities. Targeted delivery of mesoporous silica nanoparticles (MSNs) loaded with miRNA therapeutics specifically to prostate tumors may supplement androgen‐deprivation therapy, radiation therapy, or surgery.